Hope, harmony and humanity: creating a positive social climate in a democratic therapeutic community prison and the implications for penal practice. Issue 1 (7th December 2017) - Bennett, Jamie; Shuker, Richard
Abstract : Purpose: There has been growing attention given to the concept of social climate as an element of prison practice. Research has indicated that more positive social climates can improve safety, psychological well-being, quality of life and contribute towards reduced reoffending. The purpose of this paper is to consider how the more positive social climates found in democratic therapeutic communities are constructed and how these practices can be replicated in other settings. Design/methodology/approach: This paper adopts a reflective practice approach. The intention is to look back at the concept of social climate in prisons and in particular within a prison-based democratic therapeutic community (DTC); draw upon research and theory in order to critically evaluate the nature and effectiveness of that social climate, and; draw wider lessons about the nurturing and maintenance of social climates that may have broader relevance in prisons. Findings: It is concluded that understanding and managing social climate is an essential aspect of improving the safety and effectiveness of prisons. Developing practices that enhance social climate requires looking beyond mainstream prison practices, towards niches such as specialist units and prisons, including DTCs and other therapeutic communities, and psychologically informed environments, as well as looking at practices in other settings including forensic mental health. Taking this wider perspective can be source of ideas and practice that could inform a profound culture change. Originality/value: The paper offers an attempt to understand the distinct practices that create a more positive social climate in DTCs and consider how elements of this could be exported to other prisons. This has implications for both penal theory and practice.